Temperature‐regulated gold nanoparticle sensors for immune chromatographic rapid test kits with reproducible sensitivity: a study. Issue 3 (3rd March 2021) - Manta, Prince; Chandra Singh, Suresh; Deep, Aman; Kapoor, Deepak N.
Abstract: Immune‐chromatographic kits are being used since several years in the rapid detection of infectious diseases. It is also called the lateral flow technique, and is used for antigen or antibody detection. There are a series of steps involved in the development of these immune‐chromatographic test kits. Still, the preparation of gold nanoparticles (AuNPs) is an important quality variable for the immune‐chromatographic test kit sensitivity. The immune chromatographic test must be specific in detection for specific antigen and antibody; this implies that the test kit should not show a false result. Secondly, the test kit should be sensitive enough to give a readable result, and the intensity of the test line should increase or decrease with the concentration of an analytic sample. Various factors can influence the performance of a test. Temperature differences in AuNPs preparation can alter the assay kinetics and contribute to assay variability. Other factors such as assay components, manufacturing processes and reagent variation also contribute to assay precision and accuracy. It is important to note that assay reproducibility is the combined effect of individual sources of variability. The authors have synthesized AuNPs by immediately controlling the reaction temperature. Different batches of Malaria rapid test kit were developed and the test kit sensitivity was analysed. It was found that test kits designed with temperature‐controlled AuNPs sensor had reproducible uniformity in terms of batch to batch sensitivity than AuNPs synthesized by conventional Turkevich and Fern process.